Patients’ satisfaction with the quality healthcare services - Tamara Milosavljević; Nina Stoičević; Dragan Ivanović (Биомедицинска истраживања, 2024)
The quality of health services has become a priority in the modern health system, defined as a service that meets professional and patient needs by efficiently using resources and minimizing risks. The quality of health care implies the best possible outcomes, timely service, rational use of resources and application of appropriate procedures. Quality measurement includes dimensions such as availability, safety, continuity, effectiveness and interpersonal relationships, key to patient trust and satisfaction. This literature Reviews analyzes instruments for measuring the quality of health services and their importance for improving the system. Satisfaction is not a sufficient indicator of quality, because patients are often unaware of their real needs and may demand inadequate treatments. Quality also includes economy and compliance with legal, ethical and contractual obligations of the healthcare institution. Major satisfaction factors include healthcare, communication, waiting time and patient education. Patient satisfaction should be measured regularly and used for continuous improvement of services. The quality of health care is a continuous process that requires constant monitoring, evaluation and improvement to ensure the best possible outcome for patients.
Keywords: patient satisfaction; healthcare; quality